Comparison of the Legality and Legal Power of Conventional and Electronic Land Certificates in the Land System in Indonesia - Hemas Mardikawati, Trisakti; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
This study aims to analyze: 1) Comparison of the legality between conventional land certificates and electronic land certificates in the land system in Indonesia. 2) Comparison of the legal force of conventional land certificates and electronic land certificates in providing proof and legal protection for land rights holders. This type of research falls within the scope of normative legal research. The approach method in this research is legislation (statue approach). The type of data in this research is secondary data sourced from primary, secondary and tertiary legal materials. The data collection method uses library techniques (study document). The analysis in this research is prescriptive. The results of the research are concluded: 1) Comparison of the legality between conventional land certificates and electronic land certificates in the land system in Indonesia, namely both conventional land certificates and electronic land certificates have equal legality in the Indonesian land law system because both are the result of the land registration process as regulated in Article 19 of the UUPA, PP Number 24 of 1997, and PP Number 18 of 2021. Conventional certificates have strong but not absolute evidentiary power, while electronic certificates obtain legitimacy through the Regulation of the Minister of ATR/BPN Number 3 of 2023 and Article 5 of Law Number 1 of 2024 concerning ITE which confirms the validity of electronic documents as legal evidence. Both are legitimate state administrative decisions, so the difference between physical and digital forms does not affect their status. 2) Comparison of the legal force of conventional land certificates and electronic land certificates in providing evidence and legal protection for land rights holders, namely conventional land certificates and electronic land certificates have equal legal force in providing evidence and legal protection for land rights holders, because both are issued by authorized officials in accordance with Article 19 paragraph (2) letter c UUPA and Article 32 PP Number 24 of 1997. Conventional certificates have strong but not absolute evidentiary force and provide protection for rights holders in good faith, while electronic certificates obtain legal legitimacy through Article 6 paragraph (2) and Article 16 paragraph (2) of the Minister of ATR/BPN Regulation Number 3 of 2023, and their validity is recognized based on Article 5 of Law Number 1 of 2024 concerning ITE and are equipped with personal data protection as regulated in Law Number 27 of 2022 concerning PDP.